The Effect of Aesthetic Education on the Formation of Personal Identity of Children and Young People - Filipović, Sanja B.; Vojvodić, Milica V. (Sociološki pregled, 2019)
Today’s society, focused on prosperity, is especially interested in developing the identity of individuals. Parallel to uniformity and conformity, which lead to the current crisis of personal identity, the importance of the individual’s awareness of one’s own identity is emphasized. This dualism and cultural framework in which a young person matures largely determine and integrate his/her personality, and influence the formation and development of personal identity. In a society that fosters an emancipatory climate, conditions are created that favor the formation of self-conscious, responsible and productive members of society. The teaching of art and art classes are the ones that provide the opportunity for the development of creativity, creative communication and aesthetic development, which also affects the emancipation, socialization and development of the personal identity of pupils.
Keywords: personal identity; emancipation of personality; aesthetic education; art classes